The Basics of Genetic Constitutional Similimum - Bhide, Rajesh (Homœopathic Links, 2013)
The human organism is made up of different systems, e.g., respiratory, digestive, nervous, reproductive systems, etc. These systems are made up of organs. Organs are made up of cells. In the cell lies our genome, the very core of who we are. This differs from person to person. So, our concept of individualisation lies in understanding the genetic code of the individual; we cannot afford to neglect it! When we treat man in disease and not disease in man, we must understand the person at his very basic, cellular level, what he comprises (mentally, physically, generally, and which diseases he/she is prone to).
Keywords: Genetic constitutional similimum; Genetic case-taking; Gene; Miasm; Nitricum acidum; Psora; Sycosis; Syphilis; Heringʼs law of cure